Opportunities and Challenges in Developing Distance Education Services Open University for Indonesian Citizens in Malaysia - Taufiqurrahman Hasyim; Ali Muktiyanto; Indrianawati Usman; Wahyu Wahyu (Journal of International Conference Proceedings (JICP), 2022)
The Indonesian Open University (UT) has had extensive experience in providing, implementing, and developing educational services in Indonesian and abroad. Several problems related to the planned development of Distance Education Services (PJJ-UT), have become obstacles that hinder the smooth expansion and management of UT abroad. This paper aims to analyze the opportunities and challenges in developing PJJ-UT in Malaysia. The approach used in this study is a qualitative method. The data are collected through participant observation as well as unstructured in-depth interviews involving resources ranging from UT managers, students, and alumni. The results: (1). Many fresh graduates from Senior High School, have departed for Malaysia before the time of receiving their graduation certificate. They are constrained from realizing their intention to continue their study while working; (2). Indonesian illegal migrants who have joined as students, have limited space for movement and are being arrested by Malaysian authorities; (3). Implementation of the mandatory overtime system at workplace, prevented students from participating in examinations; (4). The distance of the student coverage area, resulted in delays in taking academic activities; (5). The dropping out phenomenon among students who are not motivated to study is high, especially after returning to their homeland. Keywords: PMI In Malaysia, PJJ Program For PMI, Study While Working.